Brand Image, e-WOM, Brand Trust, dan E-Service Quality terhadap Keputusan Pembelian Tiket Melalui Traveloka - Larasati Prastyoningrum; Eny Sulistyowati (LPPM Akademi Manajemen Administrasi Yogyakarta, 2026)
This research was conducted to examine the influence of brand image, e-WOM, brand trust, and e-service quality on ticket purchasing decisions among Traveloka consumers. A quantitative approach was applied using primary data gathered from 150 respondents collected through a purposive sampling technique. The data were gathered through Google Forms and analyzed using multiple linear regression techniques. The existing findings reveal that brand image, e-WOM, and brand trust positively and significantly affect purchasing decisions, while e-service quality does not show a significant influence. The research model is able to explain 67,5% of purchasing decisions. These findings emphasize the need to strengthen brand image, manage online reviews, and build consumer trust in shaping consumer behavior on digital platforms. This study also provides practical insights for Online Travel Agent (OTA) companies in developing increasingly effective digital marketing strategies.